2019
DOI: 10.1111/jfd.13116
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transmission of Bonamia exitiosa by cohabitation causes mortality in Ostrea angasi

Abstract: The haplosporidian Bonamia was first detected in Australian shellfish in 1991. Australian isolates in Ostrea angasi Sowerby, 1871 were identified as Bonamia exitiosa Hine, Cochennac and Berthe, 2001, which threatens development of an O. angasi aquaculture industry. European field data suggest that Bonamia ostreae Pichot, Comps, Tigé, Grizel and Rabouin, 1980 infections in Ostrea edulis Linnaeus, 1758 build slowly, but infection dynamics of B. exitiosa in O. angasi are unknown. We investigated B. exitiosa infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(75 reference statements)
1
2
0
Order By: Relevance
“…However, outside hemocytes, there was a lower abundance of cells with two nuclei. This corresponds to the previously described imprints findings of Bonamia exitiosa in flat oysters [31][32][33][34]. Histopathological examination of positive PCR samples of B. exitiosa confirmed Bonamia-like cells in one-third of samples.…”
Section: Discussionsupporting
confidence: 90%
“…However, outside hemocytes, there was a lower abundance of cells with two nuclei. This corresponds to the previously described imprints findings of Bonamia exitiosa in flat oysters [31][32][33][34]. Histopathological examination of positive PCR samples of B. exitiosa confirmed Bonamia-like cells in one-third of samples.…”
Section: Discussionsupporting
confidence: 90%
“…Survival assessment at the end of the experiment showed that survival after one year was low (17%–33%). Bonamia exitiosa infection intensities were lower (3.01–7.02 cells/heart smear) than described for O. angasi experiencing clinical B. exitiosa disease and mortality (15.40–24.20 cells/heart smear) by Buss et al (2019a). It is therefore unlikely that oysters were dying from clinical B. exitiosa infection in this study.…”
Section: Discussionmentioning
confidence: 58%
“…was identified in Australia in the early 1990s in farmed and wild populations of the Native Oyster ( Ostrea angasi , Sowerby, 1871) (see Hine & Jones, ). Extensive investigations including genome sequencing have identified all southern Australian Bonamia isolates as Bonamia exitiosa Hine, Cochennac and Berthe, 2001 (see Bradley, ; Buss, Harris, Tanner, Wiltshire, & Deveney, 2019a). Handlinger et al () reported that histological surveys of wild O. angasi across SA in 1992–93 did not detect Bonamia .…”
Section: Introductionmentioning
confidence: 99%